Elucidação da interação hóspede-hospedeiro entre R-(-)- carvona e β-ciclodextrina - Carvalho Neto, Antonio Guilherme de (2017)
The essential oils (EOs) are compounds extracted from plants that have a great variety of biological activities reported in the literature. In this class, carvone, an unsaturated ketone monoterpene, is found in nature under two enantiomeric forms: S-(+)-carvone and R-(-)-carvone. Carvone has several pharmacological properties such as anticancer, anticonvulsant, anxiolytic, antidepressant and anti-inflammatory. R-(-)-carvone has some physico-chemical characteristics that limit its use, such as low solubility in water, high volatilization and easy oxidation. In this perspective, the formation of inclusion complexes (ICs) with cyclodextrins (CDs) have been one of the main strategies to increase the solubility in water of poorly soluble drugs, bypassing their physico-chemical limitations. In this way, the present study aimed to prepare the R-(-)-carvone/β-CD complexes in the 1: 1 molar ratio by different complexation methods: physical mixture (PM), paste complex (PC), slurry complex (SC), ultrasound (US) and freeze drying (FD), characterized by differential scanning calorimetry (DSC), thermogravimetry/derivative thermogravimetry (TG/DTG), Karl Fischer Moisture Determination (KF), Fourier transform infrared spectrophotometry (FTIR), X-ray diffraction (XRD) and scanning electron microscopy (SEM). In addition, the analytical method for quantification of R-(-)-carvone was developed by high performance liquid chromatography (HPLC) and complexation efficiency (CE%) was determined from this method. DSC and TG/DTG curves of the SC and FD methods showed, respectively, the disappearance of the R-(-)-carvone melting characteristic event, and the considerable reduction of mass loss in the first step (Δm1 6.87% and 5.18% between 34-150 °C), indicating the complexation. XRD results of the ICs (PC, SC and FD) showed the disappearance of spectral characteristic lines of β-CD and the emergence of new peaks, suggesting a change of β-CD crystalline phase. SEM images of ICs exhibited relevant changes in morphology compared to free β-CD and PM, showing a decrease in particle size, especially in the US and FD methods. FTIR results showed that there were displacements and reduction in the intensity of the R-(-)-carvone characteristic bands in the ICs spectra. HPLC analysis showed that the higher CE% were obtained by SC and FD methods (70.93% and 84.26%). Thus, it is concluded that the SC and FD complexation methods presented the best host-guest interaction profiles, suggesting IC's formation between R-(-)-carvone and β-CD.